2014
DOI: 10.1007/s11032-014-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide prediction of three important traits in bread wheat

Abstract: Five genomic prediction models were applied to three wheat agronomic traits—grain yield, heading date and grain test weight—in three breeding populations, each comprising about 350 doubled haploid or recombinant inbred lines evaluated in three locations during a 3-year period. The prediction accuracy, measured as the correlation between genomic estimated breeding value and observed trait, was in the range of previously published values for yield (r = 0.2–0.5), a trait with relatively low heritability. Accuraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 36 publications
6
40
2
Order By: Relevance
“…Accordingly, genomic selection is expected to give more accurate predictions if lines included in the training population are closely related to (Asoro et al 2011; Lehermeier et al 2014; Lorenz and Smith 2015) or even come from the same population as the selection candidates (Windhausen et al 2012; Charmet et al 2014). The underlying population structure can be readily deciphered when multiple large bi-parental populations (Heffner et al 2011a; Schulz-Streeck et al 2012; Riedelsheimer et al 2013; Lehermeier et al 2014) or larger heterotic groups (Technow et al 2013; Lehermeier et al 2014; Spindel et al 2015) are directly involved in the development of varietal candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, genomic selection is expected to give more accurate predictions if lines included in the training population are closely related to (Asoro et al 2011; Lehermeier et al 2014; Lorenz and Smith 2015) or even come from the same population as the selection candidates (Windhausen et al 2012; Charmet et al 2014). The underlying population structure can be readily deciphered when multiple large bi-parental populations (Heffner et al 2011a; Schulz-Streeck et al 2012; Riedelsheimer et al 2013; Lehermeier et al 2014) or larger heterotic groups (Technow et al 2013; Lehermeier et al 2014; Spindel et al 2015) are directly involved in the development of varietal candidates.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of FAY12 and FAY14, QTL detected in the combined analysis (i.e., stable QTL) were better able to explain phenotypic variation in GY across site-years, ranging from 11 to 39 %. Charmet et al (2014) reported genome-wide prediction accuracies for GY in wheat ranging from r = 0.32 to 0.70 within single RIL populations based on resampling of genotypes. Heffner et al (2011) found the prediction accuracies in a multi-family population of advanced breeding lines to be much lower (r = 0.180-0.223) but still advantageous over phenotypic selection or conventional MAS when predicting across years.…”
Section: Potential Marker Assisted Selection For Gymentioning
confidence: 99%
“…Consequently, it is relevant to enable prediction in new progeny sets across years and predict across less related breeding sets. However, this issue is a major challenge in genomic prediction in plants, since prediction accuracy between genetically unrelated populations (or families) is often low [20,21]. Investigation of genomic prediction accurracy between families is done by cross-validation strategies, where less related groups are predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of genomic prediction accurracy between families is done by cross-validation strategies, where less related groups are predicted. The authors of [21] performed cross-validation using three different wheat sets originated by different parents: two DH sets and one recombinant inbred set, and found low prediction accuracies when one set was used to predict another.…”
Section: Introductionmentioning
confidence: 99%